A Prognostic Signature Consisting of Pyroptosis-Related Genes and SCAF11 for Predicting Immune Response in Breast Cancer - Chu, Ling; Yi, Qiaoli; Yan, Yuanliang; Peng, Jinwu; Li, Zhilan; Jiang, Feng; He, Qingchun; Ouyang, Lingzi; Wu, Shangjun; Fu, Chencheng; Liu, Ying; Xu, Zhijie (Frontiers in Medicine, 2022)
Pyroptosis is characterized as an inflammasome-mediated cell death pathway that may participate in the occurrence and development of tumors. However, the underlying molecular function of pyroptosis remains unclear in BRCA. In this study, we aimed to explore a prognostic signature of BRCA based on the pyroptosis-related genes. Data was downloaded from TCGA database, and then we screened 760 female BRCA samples and 104 normal breast tissues as the training set. Seven pyroptosis-associated genes (CASP9, GPX4, IL18, NLRC4, SCAF11, TIRAP, and TNF) were identified as the pyroptosis-related prognostic model for BRCA using LASSO Cox regression. The prognostic value of pyroptosis-associated gene signature was verified in the validation set, GSE 20685. Time-dependent receiver operating characteristic analysis demonstrated the credible predictive value of the pyroptosis-associated gene signature. The area under the curve reached 0.806 at 3 years, 0.787 at 5 years, 0.775 at 8 years, and 0.793 at 10 years in the training set, and 0.824 at 5 years, 0.808 at 8 years, and 0.790 at 10 years in the validation set. Furthermore, there are currently few data on SCAF11 regulating pyroptosis. To clarify this issue, we performed integrative bioinformatics and experimental analysis. Knocking down SCAF11 possessed an anti-cancer effect in terms of inhibiting cell viability and suppressing colony-formation in in-vitro functional assays. Meanwhile, the biological functions of SCAF11 in BRCA were further validated with several algorithms, such as Xiantao tool, LinkedOmics, GEPIA2, and TISIDB. These findings indicated that SCAF11 expression was significantly associated with a wide range of tumor-infiltrating lymphocytes (TILs), including T central memory cell (Tcm), and type 2 T helper cell (Th2), etc. Functional enrichment analysis indicated that co-expression genes of SCAF11 mainly participated in inflammation and immune-associated signaling pathways, such as oxidative phosphorylation, antimicrobial humoral response, and immunoglobulin complex. Moreover, SCAF11 expression was positively correlated with several immune checkpoints, including PD-L1, B7H3, and PDCD1LG2. Taken together, this study uncovered that pyroptosis-associated gene signature might be applied as an independent prognostic factor and effective predictor in patients with BRCA. The pyroptosis-related gene SCAF11might play potential roles in the regulation of immune microenvironment in BRCA.